ANALISIS KEPATUHAN WAJIB PAJAK BADAN PADA PERATURAN PERUNDANG-UNDANGAN PERPAJAKAN BERDASARKAN PMK NOMOR 136 TAHUN 2023 STUDI KASUS PT. ARKEN EHOWU PUTRA MOTOR - Tafonao, Erdin Juniman; Zai, Kurniawan Sarototonafo; Zebua, Dedi Irawan; Zebua, Fakta Solala (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
This study aims to analyze the level of corporate taxpayer compliance with tax regulations based on PMK Number 136 of 2023, with a case study at PT. Arken Ehowu Putra Motor. The research method used is quantitative descriptive with data collection through interviews and surveys. The results of the study indicate that PT. Arken Ehowu Putra Motor has a high level of compliance with tax regulations, although there are several areas that need improvement, especially in terms of timely tax reporting and payment. Factors that influence this compliance include taxpayer understanding of the regulations, the effectiveness of the tax administration system, and supervision from the tax authorities. This study concludes that increasing socialization and training can further improve corporate taxpayer compliance.